The MachMoS Node: A Low-Cost Open-Access Vibro-Acoustic Sensor for Machine Condition Monitoring in the Age of Artificial Intelligence - Tremblay, Simon Jonathan (Université d'Ottawa / University of Ottawa, 2026)
Machine Condition Monitoring and Prognostics and Health Management are long-standing industrial fields that have not yet fully benefited from the widespread adoption of artificial intelligence. Research in these areas is hindered by the limited availability of open-access machine health data required to train artificial intelligence models. This work proposes that by making machine monitoring more affordable, the acquisition of large volumes of machine health data across industrial systems can be significantly expanded. To this end, this thesis describes the design, construction, and qualification of the MachMoS Node, an open-access vibro-acoustic and thermal sensor. The machine monitoring system (MachMoS) node developed in this work is cost-effective yet meets performance requirements for industrial condition monitoring applications. The thesis includes a review of relevant international standards in condition monitoring, prior research, and fundamental principles of sensors commonly used in this field. The methodology details the design and validation of the MachMoS Node against high-performance industrial sensors. The development process encompassed benchmarking against existing commercial sensors, defining requirements and specifications, component selection, electronic circuit and printed circuit board design, and mechanical enclosure design following Design for Manufacturing and Assembly principles to allow production by research institutions or basic machine shops, as Moreover, simulations addressing acoustic, thermal, and power-management considerations were conducted. These analyses ensure over one year of sensor operation between charges, predicted enclosure-induced resonance in agreement with experimental measurements, and provided a thermal model that allows sensor readings to be compensated for, enabling more accurate machine temperature estimations. The resulting device is a rechargeable, wireless, vibro-acoustic and thermal monitoring node. Its performance was validated through laboratory testing, including accelerometer and acoustic frequency-response analysis, temperature calibration in an ice bath, an ingress protection assessment, and evaluation of energy usage, charging circuitry, wireless range, and external sensor connectivity. Future work will include comprehensive electromagnetic interference and compatibility testing, extended temperature evaluation, further cost optimisation, code optimisations, and long-term industrial deployment as part of a complete monitoring system.
Keywords: Hardware Design; Vibro-Acoustic Sensor; Accelerometer; Vibration; Machine Condition Monitoring; MCM; Internet of Things; IoT; Ingress Protection; Open-Access; Microphone; MEMS; Design; DFMA